2020
DOI: 10.1001/jamadermatol.2019.3617
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Multiple Dupilumab Dose Regimens After Initial Successful Treatment in Patients With Atopic Dermatitis

Abstract: The dupilumab regimen of 300 mg every 2 weeks is approved for uncontrolled, moderate to severe atopic dermatitis (AD). OBJECTIVE To assess the efficacy and safety of different dupilumab regimens in maintaining response after 16 weeks of initial treatment. DESIGN, SETTING, AND PARTICIPANTS The Study to Confirm the Efficacy and Safety of Different Dupilumab Dose Regimens in Adults With Atopic Dermatitis (LIBERTY AD SOLO-CONTINUE) was a randomized, double-blind, phase 3 clinical trial conducted from March 25, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
196
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(203 citation statements)
references
References 36 publications
3
196
3
1
Order By: Relevance
“…Nine additional articles were suggested by the GDG group but excluded due to dose not approved by the regulatory authorities, non-randomised double-blind study design, not reporting outcomes of interests, or duplicate data (Table S3). The SR for the efficacy and safety included seven RCTs (36,37,38,39,40,41) ( figure 1A). For the economic evidence, after screening 1552 hits, five studies were considered suitable for inclusion (51,52, 53, 54,55) (figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine additional articles were suggested by the GDG group but excluded due to dose not approved by the regulatory authorities, non-randomised double-blind study design, not reporting outcomes of interests, or duplicate data (Table S3). The SR for the efficacy and safety included seven RCTs (36,37,38,39,40,41) ( figure 1A). For the economic evidence, after screening 1552 hits, five studies were considered suitable for inclusion (51,52, 53, 54,55) (figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled analysis showed that dupilumab reduces symptoms of anxiety and depression with high certainty of evidence in adults (MD -3.08; 95%CI -4.41 to -1.75) and with moderate certainty in adolescents (MD -1.30; 95%CI -3.38 to +0.78). In the 36 weeks follow-up of SOLO trials an opposite effect was reported (MD 0.31, 95%CI 0.04 to 0.57) (41). Two RCTs (38,39)) evaluated this outcome as the proportion of the patients with no clinically relevant symptoms of anxiety and depression at 16 weeks (RR 1.78; 95% CI 1.35 to 2.33) and one of the two RCTs reported a better effect at 52 weeks (RR 2.40; 95%CI 1.5 to 3.87) (38).…”
Section: Anxiety and Depressionmentioning
confidence: 92%
See 3 more Smart Citations